Analysis of Multi-Project Resources in Dam Construction on Java Island Affecting Contractor Performance - Indriawan Subagyo; Muhammad Isradi (Eduvest - Journal of Universal Studies, 2025)
The construction of dams is part of a national strategic project that requires optimal resource management in order to improve contractor performance. This study aims to analyze the influence of various project resource factors—such as human resources, materials, equipment, implementation methods, information technology, and the environment—on the performance of contractors in dam projects in Java. The research method used is quantitative with the Partial Least Square-Structural Equation Modeling (PLS-SEM) and Importance Performance Analysis (IPA) approaches. Data collection was carried out through the distribution of questionnaires to 125 respondents who were directly involved in four dam projects, namely the Cijurey, Jragung, Cabean, and Bago Dams. The results of the analysis show that not all resource variables have a significant effect on the performance of contractors. The variables that have a significant influence both in terms of importance and performance are equipment, implementation methods, and environment, while human and material resources do not have a significant influence. These findings confirm the importance of optimizing the management of equipment and working methods as well as adjusting to the project's environmental conditions. This research makes a practical contribution in the management of multi-dam projects, especially in determining the priority scale of resource management that has an impact on improving the overall performance of contractors.